Test device for spare wheel carrier detection and test method thereof - ZHOU YOUMING; LI DEGUANG; LAN JUN; LI JUN; FANG SHILONG; WANG LIJUAN; LU KAIYANG (2022)
The invention provides a testing device for spare wheel carrier detection and a testing method thereof, and relates to the field of spare wheel carrier testing. The test device comprises a test bench, a supporting structure, a frame structure and a sensor assembly, the supporting structure is fixedly installed on the upper side of the test bench, and the frame structure is fixedly installed on the supporting structure; the frame structure comprises two longitudinal beams and two cross beams, the cross beams are fixedly connected between the two longitudinal beams, reinforcing parts are arranged between the longitudinal beams and the supporting structure, and assembling holes for fixing the spare wheel carrier are formed in the lower sides of the longitudinal beams; the sensor assembly comprises a first sensor, a second sensor and a third sensor, and the second sensor is installed on the frame structure to detect the vibration acceleration of the frame structure; the third sensor is used for being installed on